2020
DOI: 10.1109/tac.2019.2930239
|View full text |Cite
|
Sign up to set email alerts
|

Input-to-State Stability of Time-Delay Systems With Delay-Dependent Impulses

Abstract: This paper studies input-to-state stability (ISS) of general nonlinear time-delay systems subject to delay-dependent impulse effects. Sufficient conditions for ISS are constructed by using the method of Lyapunov functionals. It is shown that, when the continuous dynamics are ISS but the discrete dynamics governing the delay-dependent impulses are not, the impulsive system as a whole is ISS provided the destabilizing impulses do not occur too frequently. On the contrary, when the discrete dynamics are ISS but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 35 publications
0
45
0
Order By: Relevance
“…Additionally, [165] considered ISS of IDSs with distributed-delayed impulses. Moreover, [86,103] studied the effect of delaydependent impulses on ISS of nonlinear systems. It is shown that the delay in impulses may bring a destabilizing effect to the ISS property of nonlinear systems with delay-dependent impulses.…”
Section: 2mentioning
confidence: 99%
“…Additionally, [165] considered ISS of IDSs with distributed-delayed impulses. Moreover, [86,103] studied the effect of delaydependent impulses on ISS of nonlinear systems. It is shown that the delay in impulses may bring a destabilizing effect to the ISS property of nonlinear systems with delay-dependent impulses.…”
Section: 2mentioning
confidence: 99%
“…Recently, ISS analysis for impulsive systems mainly focused on delayed impulsive systems. Some representative results were reported in [37][38][39][40][41][42] for continuous-time delayed impulsive systems and [43] for discrete-time delayed impulsive systems.…”
Section: Review On Input-to-state Stability (Iss) Of Impulsive Systemsmentioning
confidence: 99%
“…In [39,40], sufficient conditions in terms of exponential ISS-Lyapunov functions equipped with an appropriate dwell-time condition were established for ISS of impulsive systems and their networks. In [42], ISS conditions were derived for time-delayed systems with delay-dependent impulses.…”
Section: Review On Input-to-state Stability (Iss) Of Impulsive Systemsmentioning
confidence: 99%
“…Complex networks have been extensively studied over the past few decades because complex dynamical networks (CDNs) have been widely applied to many fields, such as optimization problem, biology, signal processing, and industrial automation 1-5 . For these applications, complex networks strongly depend on the dynamic behavior of the network, such as stability, 6 dissipativity, 7 and synchronization 8,9 . Particularly, the synchronization problem on CDNs, as a significant dynamic phenomenon, was carried out by two pioneering works; 10,11 such an issue has become a hot research topic.…”
Section: Introductionmentioning
confidence: 99%